Penerapan Pijat Oksitosin dalam Meningkatkan Produksi ASI pada Ibu Post Partum Sectio Caesarea: Case Report - Inti Nur Rohmah; Yuni Purwati (Lembaga Pengembangan Kinerja Dosen, 2026)
Optimal breast milk production is a major factor in the success of exclusive breastfeeding, but postpartum mothers with cesarean sections often experience suboptimal breast milk production due to ineffective oxytocin hormone stimulation after surgery. Non-pharmacological interventions such as oxytocin massage are reported to stimulate oxytocin hormone secretion, thereby facilitating the let-down reflex and increasing the volume of breast milk available to the baby. The purpose of this case report is to determine the results of the application of oxytocin massage to increase breast milk production in postpartum mothers at PKU Muhammadiyah Gamping Hospital. The case study method focuses on providing nursing interventions to evaluate the results of the intervention in 1 respondent of postpartum cesarean section patients. Data were collected through interviews and observations of postpartum mothers. The results of observations showed a significant increase in optimal breast milk output reaching 80-100 ml and signs of successful breastfeeding such as increased breastfeeding frequency and signs of satiety in the baby. This intervention is concluded to be effective as part of nursing care to address suboptimal breast milk production in postpartum mothers with cesarean sections.